Westonci.ca is the premier destination for reliable answers to your questions, brought to you by a community of experts. Connect with a community of experts ready to provide precise solutions to your questions on our user-friendly Q&A platform. Get quick and reliable solutions to your questions from a community of experienced experts on our platform.
Sagot :
Let's analyze each of the given relations step-by-step to determine their gradients and y-intercepts.
### Part a: [tex]\( y = 2x - 4 \)[/tex]
This equation is already in the slope-intercept form, which is [tex]\( y = mx + b \)[/tex].
- The slope (or gradient) is the coefficient of [tex]\( x \)[/tex]. Here, [tex]\( m = 2 \)[/tex].
- The y-intercept is the constant term, which is the value of [tex]\( y \)[/tex] when [tex]\( x = 0 \)[/tex]. Here, [tex]\( b = -4 \)[/tex].
So for [tex]\( y = 2x - 4 \)[/tex]:
- Gradient (slope) = 2
- Y-intercept = -4
### Part b: [tex]\( x + 3y = 6 \)[/tex]
For this equation, we need to rearrange it into the slope-intercept form [tex]\( y = mx + b \)[/tex].
Starting from:
[tex]\[ x + 3y = 6 \][/tex]
Step 1: Isolate the [tex]\( y \)[/tex]-term by moving [tex]\( x \)[/tex] to the other side:
[tex]\[ 3y = -x + 6 \][/tex]
Step 2: Solve for [tex]\( y \)[/tex] by dividing every term by 3:
[tex]\[ y = -\frac{1}{3}x + 2 \][/tex]
Now, the equation is in slope-intercept form [tex]\( y = mx + b \)[/tex]:
- The slope (or gradient) is the coefficient of [tex]\( x \)[/tex]. Here, [tex]\( m = -\frac{1}{3} \)[/tex].
- The y-intercept is the constant term, which is the value of [tex]\( y \)[/tex] when [tex]\( x = 0 \)[/tex]. Here, [tex]\( b = 2 \)[/tex].
So for [tex]\( x + 3y = 6 \)[/tex]:
- Gradient (slope) = -[tex]\(\frac{1}{3}\)[/tex]
- Y-intercept = 2
### Summary of Results
1. For [tex]\( y = 2x - 4 \)[/tex]:
- Gradient (slope) = 2
- Y-intercept = -4
2. For [tex]\( x + 3y = 6 \)[/tex]:
- Gradient (slope) = -[tex]\(\frac{1}{3}\)[/tex]
- Y-intercept = 2
### Sketching the Graphs
To sketch the graphs of these two equations:
1. [tex]\( y = 2x - 4 \)[/tex]:
- Start at the y-intercept (-4) on the y-axis.
- From this point, use the slope to determine the next point. Since the slope is 2, for every 1 unit you move to the right on the x-axis, move 2 units up.
2. [tex]\( x + 3y = 6 \)[/tex]:
- Start at the y-intercept (2) on the y-axis.
- From this point, use the slope to determine the next point. Since the slope is -[tex]\(\frac{1}{3}\)[/tex], for every 3 units you move to the right on the x-axis, move 1 unit down. Alternatively, for every 1 unit you move to the right, move [tex]\( \frac{1}{3} \)[/tex] unit down.
By plotting these points and drawing the lines through them, you will obtain the respective graphs of the given relations.
### Part a: [tex]\( y = 2x - 4 \)[/tex]
This equation is already in the slope-intercept form, which is [tex]\( y = mx + b \)[/tex].
- The slope (or gradient) is the coefficient of [tex]\( x \)[/tex]. Here, [tex]\( m = 2 \)[/tex].
- The y-intercept is the constant term, which is the value of [tex]\( y \)[/tex] when [tex]\( x = 0 \)[/tex]. Here, [tex]\( b = -4 \)[/tex].
So for [tex]\( y = 2x - 4 \)[/tex]:
- Gradient (slope) = 2
- Y-intercept = -4
### Part b: [tex]\( x + 3y = 6 \)[/tex]
For this equation, we need to rearrange it into the slope-intercept form [tex]\( y = mx + b \)[/tex].
Starting from:
[tex]\[ x + 3y = 6 \][/tex]
Step 1: Isolate the [tex]\( y \)[/tex]-term by moving [tex]\( x \)[/tex] to the other side:
[tex]\[ 3y = -x + 6 \][/tex]
Step 2: Solve for [tex]\( y \)[/tex] by dividing every term by 3:
[tex]\[ y = -\frac{1}{3}x + 2 \][/tex]
Now, the equation is in slope-intercept form [tex]\( y = mx + b \)[/tex]:
- The slope (or gradient) is the coefficient of [tex]\( x \)[/tex]. Here, [tex]\( m = -\frac{1}{3} \)[/tex].
- The y-intercept is the constant term, which is the value of [tex]\( y \)[/tex] when [tex]\( x = 0 \)[/tex]. Here, [tex]\( b = 2 \)[/tex].
So for [tex]\( x + 3y = 6 \)[/tex]:
- Gradient (slope) = -[tex]\(\frac{1}{3}\)[/tex]
- Y-intercept = 2
### Summary of Results
1. For [tex]\( y = 2x - 4 \)[/tex]:
- Gradient (slope) = 2
- Y-intercept = -4
2. For [tex]\( x + 3y = 6 \)[/tex]:
- Gradient (slope) = -[tex]\(\frac{1}{3}\)[/tex]
- Y-intercept = 2
### Sketching the Graphs
To sketch the graphs of these two equations:
1. [tex]\( y = 2x - 4 \)[/tex]:
- Start at the y-intercept (-4) on the y-axis.
- From this point, use the slope to determine the next point. Since the slope is 2, for every 1 unit you move to the right on the x-axis, move 2 units up.
2. [tex]\( x + 3y = 6 \)[/tex]:
- Start at the y-intercept (2) on the y-axis.
- From this point, use the slope to determine the next point. Since the slope is -[tex]\(\frac{1}{3}\)[/tex], for every 3 units you move to the right on the x-axis, move 1 unit down. Alternatively, for every 1 unit you move to the right, move [tex]\( \frac{1}{3} \)[/tex] unit down.
By plotting these points and drawing the lines through them, you will obtain the respective graphs of the given relations.
Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. Thank you for visiting Westonci.ca, your go-to source for reliable answers. Come back soon for more expert insights.